Lean Manufacturing Tools and Their Benefits in Industries – A Systematic Review of the Literature - Gonzales Abanto, Wilson; Quispe Vasquez, Luis Roberto; Alcalde Canto, Alanis Nicoll; Delgado Saucedo, Edwar David; Marin Atalaya, Maykol Smyth Fhoresdan; Sanchez Llanos, Rosa Elizabeth; Mantilla Ocas, Clemente (LACCEI, 2024)
The objective of the systematic review was to analyze the benefits of lean Manufacturing in industries, in order to understand and synthesize the connection between these two variables. The PRISMA methodology was used. Searching for articles in English and Spanish, 21 research papers were extracted from databases such as Scopus, Proquest, Scielo and Web of Science dating from 2013 to 2022, using the key terms: “Lean Manufacturing” , “Lean Production”, “Benefits”, “Lean Manufacturing”, “Lean Production”. Research was then excluded through the Identification, selection, eligibility and inclusion phases. It has been found that lean Manufacturing tools such as 5S, VSM, Kanban, Kaizen, JIT, TPM and SMED applied to different industrial sectors provide benefits such as the reduction of cycle times, costs, reprocessing and activities that do not add value, as well as increase productivity, efficiency, quality and performance.